2020
DOI: 10.1038/s41598-020-72644-w
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution crystal structure and biochemical characterization of a GH11 endoxylanase from Nectria haematococca

Abstract: Enzymatic degradation of vegetal biomass offers versatile procedures to improve the production of alternative fuels and other biomass-based products. Here we present the three-dimensional structure of a xylanase from Nectria haematococca (NhGH11) at 1.0 Å resolution and its functional properties. The atomic resolution structure provides details and insights about the complex hydrogen bonding network of the active site region and allowed a detailed comparison with homologous structures. Complementary biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 56 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…S5) showed that FsmGH11.3 had the highest sequence similarity (44.1%) with NhGH11 (GenBank accession no. XP_003050975.1 ), a β-1,4-xylanase from GH11 in F. vanettenii was proven to decompose various xylan substrates ( 29 ). This implied that FsmGH11.3 and NhGH11 may share similar enzymatic hydrolysis of xylan.…”
Section: Resultsmentioning
confidence: 99%
“…S5) showed that FsmGH11.3 had the highest sequence similarity (44.1%) with NhGH11 (GenBank accession no. XP_003050975.1 ), a β-1,4-xylanase from GH11 in F. vanettenii was proven to decompose various xylan substrates ( 29 ). This implied that FsmGH11.3 and NhGH11 may share similar enzymatic hydrolysis of xylan.…”
Section: Resultsmentioning
confidence: 99%
“…GH11 xylanase. N. haematococca GH11 xylanase (GH11) was produced and purified as described previously (Andaleeb et al, 2020). For crystallization, the original conditions were modified to obtain microcrystals.…”
Section: Methodsmentioning
confidence: 99%
“…For GH11, we processed data with CrystFEL as described above, with the addition that during the partialator step we used both the 'unity' and the 'xsphere' partiality models for comparative reasons. The structure of GH11 (PDB entry 6y0h; Andaleeb et al, 2020) obtained under cryogenic conditions was used as the initial model and refinement was carried out essentially as described above, but without TLS-refinement. For the detailed investigation of the relation of data quality and length of data collection/indexed patterns, phenix.refine was used with exactly the same parameters and without manual intervention.…”
Section: Structure Solution and Refinementmentioning
confidence: 99%
See 1 more Smart Citation
“…In recently published work, the GC11 xylanase from Nectria haematococca (NhGC11) has been investigated with regard to substrate binding and known inhibitors (Andaleeb, 2021). However, for all compounds, soaking a monoclinic crystal of NhGC11 (Andaleeb et al, 2020) did not lead to electron density, hinting at the presence of a ligand in its known binding site. The author attributed this to the dense packing of the monoclinic crystal structure with a low Matthews coefficient of 1.9 A ˚3 Da À1 and narrow solvent channels.…”
Section: Gc11 Xylanase From Nectria Haematococca a Nonsoakable Structurementioning
confidence: 97%